Effect of fluoride on oral health status among general population residing in high- and low-level fluoride blocks in Erode District, Tamil Nadu, India: A cross-sectional study - V Gousalya; D Prabu; M Raj Mohan; Dinesh Dhamodhar; V V Bharathwaj; R Sindhu; S Sathiyapriya (Journal of Pharmacy and Bioallied Sciences, 2023)
Aim: The aim of this study was to evaluate the fluoride levels in groundwater and their effect on oral health status among the general population of Erode district, Tamil Nadu, India. Materials and Methods: A descriptive cross-sectional study was conducted among the general population of index age groups 5, 12, 15, 35–44, and 65–74 years. A total of 540 subjects participated in the study. High fluoride blocks of Erode district were selected based on the Central Ground Water Board (CGWB), Ministry of Jal Shakti, Department of Water Resources, River Development and Ganga Rejuvenation, Government of India, 2010, and the low fluoride were taken from the Groundwater Year Book (GWYB) of Tamil Nadu and UT of Puducherry, 2018. The Oral Health Assessment Form 2013 (adult and children) of the World Health Organization (WHO) was used to assess dental caries and enamel fluorosis. Clinical examination was performed using a mouth mirror and explorer under natural illumination by a single examiner. Data obtained were processed and analyzed using IBM SPSS Statistics version 26. A Chi-squared test was employed to analyze the difference between the high and low fluoride blocks. A P value of 0.05 was set to be statistically significant. Results: The current study had a contrary finding with the CGWB on water quality analysis of fluoride levels in drinking water for high fluoride block, Ammapet (1.12 ppm) and Anthiyur (1.08 ppm). The prevalence of enamel fluorosis in high fluoride block Ammapet was 44.4% and Anthiyur was 54.8%. The prevalence of dental caries in high fluoride block Ammapet was 45.9% and in Anthiyur was 43%. The prevalence of enamel fluorosis in low fluoride block Bhavanisagar was 27.4% and in Gobichettipalayam was 28.2%. The prevalence of dental caries in low fluoride block Bhavanisagar was 61.5%, and in Gobichettipalayam was 54.8%. Conclusion: This study's contradictory finding emphasizes the importance of drinking water; sanitation staff should monitor and report water fluoridation data on a monthly basis in accordance with the Water Fluoridation Reporting System, and CGWB should plan and organize a team for the upgradation of water quality in India. The National Program for Prevention and Control of Dental Diseases should look on to the endemic areas for the prevention of dental fluorosis, which should be assessed, implemented, and monitored by the public health dentist who should be recruited as oral health program officers in both central and state governments.